Gender Differences in Shopping Cart Abandonment: Evidence from Indonesia - Eka Dewi Setia Tarigan; Alfifto Alfifto; Khairunnisak Khairunnisak; Yulianita Yulianita (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2026)
Background: Shopping cart abandonment (SCA) remains a persistent challenge in e-commerce. Consumers frequently leave purchases incomplete due to psychological, technical, economic, and contextual factors. However, limited research has examined how demographic characteristics, particularly gender, shape abandonment behavior. Purpose: This research investigates the antecedents of SCA in Indonesia’s e-commerce context and examines differences in these factors between male and female consumers within the Theory of Planned Behavior (TPB) framework. Method: A quantitative research design was employed, using survey data from 300 Indonesian e-commerce users (147 males and 153 females). Data were collected via an online questionnaire and analyzed using multiple regression. Separate regression models were estimated to compare the influence of psychological, technical, economic, and contextual factors across gender groups. Findings: The results reveal distinct gender-based patterns. For women, psychological and economic factors exert stronger effects on SCA, with emotional ambivalence and price sensitivity emerging as dominant predictors. For men, technical factors, particularly checkout friction and website performance, play a more prominent role. These findings indicate differences in emotional, cognitive, and control-related evaluations in online shopping. Conclusions: Gender-specific factors shape SCA behavior in Indonesia, with women more influenced by psychological and economic considerations, while men respond more strongly to technical barriers. Research implication: This research provides practical guidance for e-commerce platforms to implement gender-responsive strategies, such as emotional reassurance and pricing transparency for women and streamlined checkout processes for men, to reduce abandonment and improve conversions. Academically, the findings highlight the importance of incorporating gender differences when applying the Theory of Planned Behavior to online consumer behavior.